Wood Frog and Boreal Chorus Frog Distribution and Habitat Associations in Wapusk National Park, Cape Churchill, Manitoba: 2004 Summary Report - Boal, Clint W; Andersen, David E; Reiter, Matthew E; Reichert, Brian (2004)
Distribution, abundance, population dynamics, and habitat relationships of anurans that inhabit sub-arctic regions are poorly understood. In addition, concern about amphibian populations at a global scale has resulted in recent efforts to establish monitoring programs for amphibians in North America (e.g., North American Amphibian Monitoring Program) and elsewhere. In an attempt to assess anuran abundance, distribution, and habitat associations in Wapusk National Park in the Cape Churchill region of Manitoba, we conducted 4 3-km transect surveys in 2002 (Boal and Andersen 2003) on the Nestor One Study Area. We detected both boreal chorus frogs (Pseudacris maculata) and wood frogs (Rana sylvatica), but also assessed survey methodology for application to the study area (Boal and Andersen 2003). In 2004, we conducted more extensive surveys to (1) further develop anuran survey protocols suitable for describing distribution and estimating abundance for anurans in sub-arctic areas (Wapusk National Park specifically), (2) assess distribution of anurans at a wider scale than was done in 2002, and (3) assess anuran distribution and abundance near Cape Churchill.